(3EOGQI GdehGQO aj Xd eJZjQGJ GdYUQs - (3haGA aDGO(B, (3TdHjs; (3GjfGS eGgQ HOjQ(B, (3MfGf SGej eMeOs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2009)
(3eGgjI EOGQI GdehGQO GdGSQjI , GJNGP GdbQGQGJ aj eMjW GdGSQI , Gdbje h GdeSJhjGJ h GdGgOGa, LhGfH GdYedjI GdGOGQjI, ehGQO GdGSQI ,YhGed JDKQ aj GSJNOGe ehGQO GdGSQI , GOGQI GdehGQO GdHTQjI , GOGQI GdehGQO ZjQ GdHTQjI , JHSjW GdGYeGd aj VhA CHYGOg GdKdGKI (B: (3GdYed , GdbGFe HGdYed , ecGf GdYeds
(3eQGLY U(B.221 (3;JWHjbGJ U(B.215s
Keywords: (3GdEOGQI GdefRdjIs; (3GdEbJUGO GdefRdjs; (3GdJOHjQ GdefRdjs